The function of histone methylation and acetylation regulators in GBM pathophysiology - McCornack, Colin; Woodiwiss, Timothy; Hardi, Angela; Yano, Hiroko; Kim, Albert H. (Frontiers in Oncology, 2023)
Glioblastoma (GBM) is the most common and lethal primary brain malignancy and is characterized by a high degree of intra and intertumor cellular heterogeneity, a starkly immunosuppressive tumor microenvironment, and nearly universal recurrence. The application of various genomic approaches has allowed us to understand the core molecular signatures, transcriptional states, and DNA methylation patterns that define GBM. Histone posttranslational modifications (PTMs) have been shown to influence oncogenesis in a variety of malignancies, including other forms of glioma, yet comparatively less effort has been placed on understanding the transcriptional impact and regulation of histone PTMs in the context of GBM. In this review we discuss work that investigates the role of histone acetylating and methylating enzymes in GBM pathogenesis, as well as the effects of targeted inhibition of these enzymes. We then synthesize broader genomic and epigenomic approaches to understand the influence of histone PTMs on chromatin architecture and transcription within GBM and finally, explore the limitations of current research in this field before proposing future directions for this area of research.